Appointee for academic year 2009-2010 - De La Salle University, Manila (Animo Repository, 2009)
Perla T. Garcia was appointed Director, DLSU Centennial Office, Jose Miguel G. Lisbona as Director, Graduate Admissions Office, Dr. Leila Calderon-Kabigting as Vice Dean of the Ramon V. del Rosario Sr. Graduate School of Business, Lysander P. Rivera as Vice Dean, Student Affairs and Maria Paz Isabel C. Trinidad as Director, Undergraduate Admissions Office for AY 2009-2010.